New records of Neogene Xenarthra (Mammalia) from eastern Puna (Argentina): diversity and biochronology. (November 2019) - Quiñones, Sofía I.; Miño-Boilini, Ángel R.; Zurita, Alfredo E.; Contreras, Silvina A.; Luna, Carlos A.; Candela, Adriana M.; Camacho, María; Ercoli, Marcos D.; Solís, Natalia; Brandoni, Diego
Abstract: Xenarthra is an endemic South American lineage of mammals, probably the sister clade of the other placental mammals. The oldest records of Xenarthra are from the latest Paleocene, although its current diversity is much lower than that recorded in some intervals of the Cenozoic Era. A new Neogene Xenarthra (Pilosa and Cingulata) assemblage from two localities of the Argentine Eastern Puna (Calahoyo and Casira) is described. The newly recorded taxa—Cingulata, Dasypodidae, Eutatini: Stenotatus sp. indet. and Eutatini indet., Euphractini: Macrochorobates scalabrinii (Moreno and Mercerat, 1891), and Tardigrada, Mylodontinae: cf. Simomylodon sp. indet. and Simomylodon cf. S. uccasamamensis Saint-André et al., 2010—and those already published from Calahoyo—Cingulata: Macrochorobates chapadmalensis (Ameghino, 1908), Eosclerocalyptus sp. indet., and Tardigrada, Megatheriidae: Pyramiodontherium bergi (Moreno and Mercerat, 1891)—suggest a middle–late Miocene age for the fossil-bearing levels. In Calahoyo, the presence of Stenotatus sp. indet., in addition to some rodents currently under study in the lower levels, suggest a closer similarity with the palaeofauna of Cerdas (southern Bolivia), probably involving the last part of the Miocene Climatic Optimum. The Xenarthra recorded in the middle and upper levels of Calahoyo and Casira suggest a late Miocene–Pliocene age. A comparative analysis between Calahoyo and Casira highlights the absence of Cingulata in the latter and a high diversity in the former. This situation probably indicates different paleoenvironmental conditions. Finally, we present the first certain record of the genus Simomylodon Saint-André et al., 2010 in Argentina, which includes the oldest record of dermal ossicles for sloths in South America.